Evaluation of the effect of different amounts of sugarcane waste compost on soil properties and sugarcane yield - NISI, ADEL; CHARM, MUSTAFA; BHATT, RAJAN; ARORA, SANJAY (Journal of Soil and Water Conservation, 2024)
Sugarcane bagasse and filter cake are byproducts of sugarcane processing. The amount of sugarcane bagasse is 30% and the filter cake is 3-4% of the total weight of milled sugarcane stalks, so a high amount of bagasse is produced in the sugar factory every year. Naturally, the process of breaking down sugarcane bagasse and filter cake is very slow due to its high lignocellulosic content. Composting is one of the solutions for processing sugarcane by-products into useful products for plants, which is compatible with the environment and economically, considering the production of compost in sugarcane cultivation and industry of Imam Khomeini in Shuaibiya region of Khuzestan and the need to use these products as Organic fertilizer to reduce the consumption of chemical fertilizers, this research on the application of compost fertilizer, which has a special application in improving the amount of soil organic matter in arid and semi-arid regions, in the form of a randomized complete block experimental design with 3 replications in different amounts with the aim Evaluation of the effect of sugarcane waste compost on soil properties and sugarcane yield in a new cultivation field was investigated. The results of this project showed that the use of 40 tons of compost per hectare compared to other treatments had a significant difference in terms of statistical analysis, so the use of compost is one of the effective solutions in improving and reducing the adverse effects of the lack of organic matter.